Sponsorship eras in the English Premier League: changing industries and globalization between 1992 and 2021. (4th July 2022) - Beek, Remco M.; Derom, Inge
ABSTRACT: The English Premier League, the elite division of association football (soccer) in England, exploited commercial opportunities and market growth since its rebranding in 1992. The companies involved in professional football sponsorships represented a variety of industries and origins. How substantial did these representations fluctuate to indicate a periodization of sponsorship eras? This paper provides a systematic and longitudinal review of shirt sponsors within the league. The investigation of historical patterns clarified the changing playing field and the current state of play of sponsorships in English football. The remarkable patterns resulted in an interconnected periodization of five sponsorship industry eras and four sponsorship globalization eras. Future sponsorship challenges were identified regarding the corporate context, community fundamentals and the level of involvement affecting new sponsorship eras. These patterns in the world-leading football competition serve as an excellent case for decision makers in other domains to recognize the dynamics in corporate community involvement.